Changes in the neutrophil-to-lymphocyte ratio predict the prognosis of patients with advanced hepatocellular carcinoma treated with sorafenib. Issue 10 (October 2019) - Hong, Young Mi; Yoon, Ki Tae; Hwang, Tae Ho; Heo, Jeong; Woo, Hyun Young; Cho, Mong
Abstract : Background and aim: Although sorafenib is the first systemic therapy to show survival benefit for advanced hepatocellular carcinoma (HCC), its survival benefit is variable for HCC. Systemic inflammation may be associated with survival in HCC. We investigated the use of systemic inflammation markers, including neutrophil-to-lymphocyte ratio (NLR), in the prognosis of sorafenib-treated HCC patients. Patients and methods: We retrospectively analyzed data of 82 patients with advanced HCC who received sorafenib as the first-line treatment. Data on pretreatment and post-treatment (2–3 months after initiating sorafenib therapy, first tumor response evaluation day) clinical, laboratory, and tumor characteristics were collected. Survival-related prognostic factors were analyzed. Results: Patients were mostly in the intermediate (12.2%) or advanced (87.8%) Barcelona Clinic Liver Cancer stages. Fifty-six (68.3%) patients had vascular invasion and 34 (41.5%) patients had extrahepatic disease. The median progression-free survival (PFS) and overall survival (OS) were 4.7 months [95% confidence interval (CI): 2.8–6.5 months] and 4.7 months (95% CI: 2.8–6.5 months). In multivariate analysis for OS, diarrhea (hazard ratio: 0.588; 95% CI: 0.348–0.993) and NLR decline (decreased compared with pretreatment) (hazard ratio: 0.479; 95% CI: 0.300–0.765) were independent factors of good OS. In the NLR decline group, the median PFS and OS were 7.1 and 7.3 months, respectively. In the NLR nondecline group, the median PFS and OS were 3.0 and 3.2 months, respectively. The difference in OS between the two groups was significant ( P = 0.004). Conclusion: A change in NLR after sorafenib therapy was associated with a better prognosis in patients with advanced HCC.